Eretrian ceramic production through time: Geometric to Hellenistic periods. (October 2018) - Charalambidou, X.; Kiriatzi, E.; Müller, N.S.; Müller Celka, S.; Verdan, S.; Huber, S.; Gex, K.; Ackermann, G.; Palaczyk, M.; Maillard, P.
Abstract: Eretria, in the centre of the Aegean (Greece), has been the focus of an interdisciplinary programme that combines macroscopic, petrographic and elemental analysis in a diachronic investigation of pottery production and supply on the site from the early third millennium (Early Bronze Age) to the end of the first millennium BCE (Hellenistic period). This paper reviews the preliminary results of the analyses of the pottery of historical times, mainly from the Geometric to the Hellenistic periods (phase II of the Eretria pottery project). It presents the compositional and technological characteristics of the local fabrics and offers examples of how continuity and innovation characterise different aspects of Eretria's pottery production. In addition, different categories of imported vessels that arrived in Eretria are investigated in order to recognize the origin of these specific products. Highlights: This paper presents the analyses of pottery of historical times from Eretria. It presents the compositional and technological characteristics of local fabrics. Our programme combines macroscopic, petrographic and elemental analysis. Certain local fabrics of historical times are similar to local Bronze Age fabrics. Continuity and innovation characterise Eretrian ceramic production through time.